Design of Mathematics Student Worksheet based on Realistic Mathematics Education Approach to Improving the Mathematical Communication Ability Students of Class VII Junior High School in Indonesia - Handayani, Ruri; man, Supar (International Journal of Engineering and Technology, 2018)
Mathematics communication is a way of sharing ideas and clarifying comprehension. The Realistic Mathematics Education (RME) approach can improve mathematical communication skills. The student worksheet is used because it is shorter, more comfortable and summarizes the material along with the questions to be able to assist students in the ability of mathematics communication. This study aims to develop teaching materials in the form of student worksheets based on Realistic Mathematics Education Approach to improve students' mathematical communication skills. This research is development research with ADDIE development model, that is analysis, design, develop, evaluation implementation. The subject of this research is the students of the first grade of VII. Instruments used in the form of validation sheet, mathematics communication ability test, and interview guidance manual. The validation sheet is addressed to material experts and media experts. The test to determine students 'mathematical communication skills is done before and after the use of student worksheet so that it is known whether there is an increase in students' mathematical communication ability. Interview guides are conducted with teachers and students to find out the curricula and character of students in the school. Data analysis techniques in this study using data reduction, presentation, and conclusion. The resulting student worksheet design based on the RME approach that matches the characteristics, curriculum, and student tasks. This research can be developed to the stage of development, implementation, and evaluation.